2021
DOI: 10.3390/ijms222010999
|View full text |Cite
|
Sign up to set email alerts
|

Exoproteome Analysis of Antagonistic Interactions between the Probiotic Bacteria Limosilactobacillus reuteri LR1 and Lacticaseibacillus rhamnosus F and Multidrug Resistant Strain of Klebsiella pneumonia

Abstract: The expansion of multiple drug resistant (MDR) strains of Klebsiella pneumoniae presents an immense threat for public health. Annually, this microorganism causes thousands of lethal nosocomial infections worldwide. Currently, it has been shown that certain strains of lactic acid bacteria (LAB) can efficiently inhibit growth of K. pneumoniae and the formation of its biofilms; however, the active principle of such action remains unknown. In the current article, the growth inhibition of MDR K. pneumoniae by two L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
(67 reference statements)
0
10
0
1
Order By: Relevance
“…The total number of leukocytes and differential cell counts in BAL samples were determined as described previously [ 13 , 14 ]. A hemocytometer was used to determine the total number of BAL and blood leukocytes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total number of leukocytes and differential cell counts in BAL samples were determined as described previously [ 13 , 14 ]. A hemocytometer was used to determine the total number of BAL and blood leukocytes.…”
Section: Methodsmentioning
confidence: 99%
“…BAL samples were obtained as described above. Blood samples were obtained via cardiac puncture and collected in heparinized tubes [ 14 , 15 ]. Cytokines determinations were performed in serum and BAL samples using commercial ELISA kits: IFN-γ (Mouse IFN-gamma Quantikine ELISA Kit, sensitivity: 2 pg/mL), and IL-10 (Mouse IL-10 Quantikine ELISA Kit, sensitivity: 5.2 pg/mL) from R&D Systems (Minneapolis, MN, USA), TNF-α (Mouse TNF alpha ELISA Kit, sensitivity: 9.1 pg/mL), IL-27 (Mouse IL-27 p28/IL30 Quantikine ELISA Kit, sensitivity: 4.7 pg/mL), IL-17 (Mouse IL-17 Quantikine ELISA Kit, sensitivity 5 pg/mL), IL-6 (Mouse IL-6 Quantikine ELISA Kit, sensitivity: 1.8 pg/mL), IL-8 mouse homolog chemokine KC (Mouse CXCL1/KC DuoSet ELISA, sensitivity 2.3 pg/mL), IL-1β (Mouse IL-1 beta ELISA Kit (ab197742), sensitivity: 1 pg/mL) and MCP-1 (Mouse MCP1 ELISA Kit (ab208979), sensitivity: 0.487 pg/mL) from Abcam (Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the exoproteome can contain proteins that bind to host or microbial receptors, which allows for the mediation of signalling 41 ; 42 . Quorum sensing molecules are also present in the exoproteome and allow bacteria to coordinate their behaviour based on population density 39 ; 43 ; 44 . Some proteins within the exoproteome can also modulate the host immune system, suppressing host defences 39 ; 45 or promoting the growth of host tissues 46 - 48 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the biophysical and biochemical comparative analysis of EVs, the authors suggested remarkable surface remodeling throughout of the T. cruzi life cycle. Savinova et al [2] focused on the antagonistic potential of two probiotic lactic acid bacteria (LAB) against MDR Klebsiella pneumoniae under co-culture conditions and used proteomic tools as to screen for major role prayers. Proteomic analysis of secreted proteins of L. reuteri LR1 and L. rhamnosus F revealed many classically or non-classically secreted proteins and suggested cell walldegrading enzymes and cell wall hydrolases as key enzymes for antagonistic interaction.…”
mentioning
confidence: 99%